Strategic Area Development to Reduce Poverty and Regional Gaps in The District - Guswandi Guswandi (Signifikan: Jurnal Ilmu Ekonomi, 2022)
Developing strategic areas utilizing existing potential will increase regional economic growth, overcome regional disparities, and reduce poverty. This study aims to determine the efficiency of district strategic area development in reducing regional disparities and poverty rates in Dharmasraya Regency for the 2016-2020 period. The results of the Data Envelopment Analysis (DEA) analysis, using the assumption that input changes are directly proportional to changes in output, show mixed results. Efficiency calculations show that investment, infrastructure, and business empowerment significantly reduce poverty and regional disparities in Dharmasraya Regency. This condition shows that developing strategic district areas can reduce regional disparities and poverty rates in Dharmasraya Regency. This research implies that it can assist the government in reducing poverty in Dharmasraya Regency by allocating funds for industrial development, expanding investment, and providing financial assistance for developing community-based creative businesses. If appropriately implemented, poverty in Dharmasraya Regency will be reduced.How to Cite:Guswandi. (2022). Strategic Area Development to Reduce Poverty and Regional Gaps in The District. Signifikan: Jurnal Ilmu Ekonomi, 11(2), 319-338. https://doi.org/10.15408/sjie.v11i2.25895.JEL Classification: R11, R58, L1